Presentation of Complex Homozygous Allele in ABCA4 Gene in a Patient with Retinitis Pigmentosa - Māreta Audere; Katrīna Rutka; Svetlana Šepetiene; Baiba Lāce (Case Reports in Ophthalmological Medicine)
Retinitis pigmentosa is a degenerative retinal disease characterized by progressive photoreceptor damage, which causes loss of peripheral and night vision and the development of tunnel vision and may result in loss of central vision. This study describes a patient with retinitis pigmentosa caused by a mutation in the ABCA4 gene with complex allele c.1622T>C, p.L541P; c.3113C>T, p.A1038V in homozygous state.